Synergetic utilization of sewage sludge and microalgae: A review and proposal. (September 2022) - Wang, Xin; Jin, Xiaodong; Wang, Hui; Hu, Zhenzhong; Shen, Boxiong
Abstract: Microalgae-based biofuel production has developed over the past few decades, but few feasible industrial systems has been established due to its negative economics. To reduce feedstock cost and increase high-value products, microalgae cultivation in wastewater has been conducted and it can apparently reduce the BOD, COD and nutrition element (N and P) in wastewater with improved biomass yield. Produced microalgae (or microalgae-bacteria granular sludge) can be converted into bioenergy by chemical, thermochemical and biological pathways. As one of wastewater treatment byproducts, sewage sludge has the similar treatment processes including dewatering, drying and biofuel conversion because of high water content. In this review, process similarity was discussed between microalgae and sewage sludge to produce bioenergy. Co-treament can simplify plant infrastructure and also effectively realize the environemntal aim of sewage sludge reduction. In the future co-dewatering, co-drying and co-treatment can be conducted for environment-enhancing biofuel production. Graphical abstract: Unlabelled Image Highlights: Co-culture of microalgae and activated sludge in wastewater treatment plants Co-culture improves microalgal biomass yield with N/P removal. Microalgae improves quality of pyrolysis products from low-value sewage sludge. Interactions between microalgae and activated sludge (bacteria) is essential. Co-dewatering and co-drying are significant research aspects.